1995
DOI: 10.1093/infdis/172.3.859
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Production of Human Immunodeficiency Virus Type 1 by In Vitro-Infected Alveolar Macrophages from Otherwise Healthy Cigarette Smokers

Abstract: Since cellular activation is required for replication of human immunodeficiency virus type 1 (HIV-1), the capacity of alveolar macrophages (AM) from smokers, which are relatively activated, and nonsmokers to support the production of HIV-1JR-FL was examined. Peak HIV-1 p24 antigen level in culture supernatants of infected AM from 13 smokers was significantly higher than that of 13 nonsmokers: 31,394 +/- 8295 versus 7037 +/- 2550 pg/mL (mean +/- SE; P < .002). This difference could not be explained on the basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 13 publications
4
39
0
Order By: Relevance
“…Such a contention is plausible based on findings that the magnitude of HIV replication is a strong predictor of the rate of progression to AIDS [68] and is supported by several in vitro studies, mentioned earlier, which have shown that smoking enhances HIV-1 replication in alveolar macrophages, microglia and T-cells [58][59][60]. It has been suggested that iron and oxidative stress are possible mechanisms of enhanced production of HIV-1 by alveolar macrophages in cigarette smokers [69,70].…”
Section: Effects Of Smoking On Hiv Disease Progression and Treatmentmentioning
confidence: 89%
See 1 more Smart Citation
“…Such a contention is plausible based on findings that the magnitude of HIV replication is a strong predictor of the rate of progression to AIDS [68] and is supported by several in vitro studies, mentioned earlier, which have shown that smoking enhances HIV-1 replication in alveolar macrophages, microglia and T-cells [58][59][60]. It has been suggested that iron and oxidative stress are possible mechanisms of enhanced production of HIV-1 by alveolar macrophages in cigarette smokers [69,70].…”
Section: Effects Of Smoking On Hiv Disease Progression and Treatmentmentioning
confidence: 89%
“…Increased permissiveness of the alveolar macrophages of smokers to HIV infection and replication in vitro have been described [58], while exposure of isolated human microglial cells [59] or TZM-bl (CD4/CCR5 co-expressing HeLa cells) and Jurkat T-cell lines [60] to nicotine or cigarette smoke extract, respectively, also augments HIV infectivity. However, to our knowledge no studies have reported possible cumulative immunosuppressive effects of HIV infection and smoking on functional indices of immune reactivity in HAART-naïve subjects.…”
Section: Cumulative Effects Of Hiv Infection and Smoking On Immunitymentioning
confidence: 99%
“…Since the prevalence of smoking is higher in HIV-1-positive individuals than in the general population (Burkhalter et al, 2005) and smoking is in turn associated with increased viral replication (Abbud et al, 1995;Rock et al, 2008;Zhao et al, 2010), it is important to understand the underlying mechanism of smoking/nicotine-mediated HIV-1 replication. This report suggests a role of nicotine metabolism in the oxidative stress-mediated increase in viral replication in HIV-1-positive smokers.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that smoking/nicotine increases HIV-1 replication in vitro, particularly in alveolar macrophages, microglia, and T cells (Abbud et al, 1995;Rock et al, 2008;Zhao et al, 2010). Since nicotine exposure has been shown to disrupt the blood-brain barrier (Manda et al, 2010), HIV-1-infected monocytes/macrophages can infiltrate the brain and infect microglia, astrocytes, and perivascular macrophages (Kedzierska and Crowe, 2002;Montaner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Smoking rates are high among individuals living with HIV (Mamary, Bahrs, & Martinez, 2002;Niaura, Shadel, Morrow, Flanigan, & Abrams, 1999). Smoking is related to reduced health-related quality of life in HIV-positive individuals and increased incidence of AIDS-defining illnesses, malignancies, mortality (Crothers et al, 2005;Kirk et al, 2007;Kohli et al, 2006;MiguezBurbano, Ashkin, & Rodriguez, 2005), and disease progression (Abbud, Finegan, Guay, & Rich, 1995;Nieman, Fleming, Coker, Harris, & Mitchell, 1993). Unfortunately, smokers living Advance Access publication May 14, 2014 nicotine & tobacco research, volume 16, number 10 (October 2014nicotine & tobacco research, volume 16, number 10 (October ) 1283nicotine & tobacco research, volume 16, number 10 (October -1288 with HIV may be less likely to quit and less motivated to quit (Gritz, Vidrine, Lazev, Amick, & Arduino, 2004;Niaura et al, 1999).…”
Section: Introductionmentioning
confidence: 99%